THE ROLE OF TEACHERS IN STUDENTS’ SUCCESS (International Conference on Education, Psychology and Humanities, 2026)
This article analyzes the role and significance of teachers in achieving students’ success. It highlights the role of teachers not only as providers of knowledge, but also as mentors and guides. It also explains how teachers’ pedagogical competence, ability to motivate, and individualized approach influence students’ development. The article further examines the importance of cooperation between teachers and students in creating an effective learning environment.
Keywords: teacher, student success, educational process, pedagogical competence, motivation, individualized approach, upbringing, knowledge delivery, quality of education, teacher–student relationship.